Legal Compliance in the Process of Independent Learning Independent Campus - Indrati Rini (East Asian Journal of Multidisciplinary Research, 2022)
In the implementation of independent learning on an independent campus, the factor of legal compliance is the main determinant of its success. The 1945 Constitution as the highest written basic law in higher education, especially in the process of independent learning on an independent campus, is carried out based on the applicable juridical method, whose legal compliance is some are obedient and some have not complied in accordance with the abilities and readiness of each university in an effort to educate the life of the Indonesian nation.